Status Mewaris Terhadap Anak Yang Lahir Dari Perkawinan Beda Agama - Ni Kadek Oktaviani; I Ketut Widia; I Ketut Sukadana (Jurnal Analogi Hukum, 2021)
The diverse in Indonesia's society is widely open for any possibility of interfaith marriages, where interfaith marriages are Nomort strictly regulated in Indonesia Marriage-Law, causing a problem that related into the validity of marriage and in the status of inherited children that are resulting biological or adopted children and affinity from this different religion marriage. The formulation of the issue and obstacle is chose in this research is about how the legal status of the interfaith marriages according to Law Number 1 Year of 1974 and how the status inherits biological or adopted children and affinity from this different religion marriages. This research is a normative legal research by reviewing legislation and using Library Research Methods the results of the research regarding interfaith marriage in Indonesia according to Marriage Act in Indonesia are Nomort strictly regulated, the consequences of this law will lead to a dilution trough a legal obscurity and uncertainty in law. But related to marital status stated in Article 2 paragraph (1) of Indonesia Marriages Law, has referred to the laws of religion and their respective beliefs faith to determine a bond of the legal marriage. As for the interfaith couples who do the marriage through the establishment of a court then recorded in the Civil Registry Office, the marriage is considered as legitimate under the government law. Legitimate marriage is a justification for a resulting of biological or adopted children and affinity to be a legitimate child. The legal status of children born of interfaith marriages is a legitimate child provided the marriage has been registered according to the statutory regulations. Regarding inheritance resulting of biological from these interfaith marriages, the children has the right to be an heir. The Marriage Law does Nomort regulate the patrimony, but moreover are regulated in more specific in each of community religion law; customary law and other laws are basically carried out by agreement by both parties.